2021
DOI: 10.3390/su13116311
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Business through Project Risk Identification with Use of Expert Estimates

Abstract: Projects are a tool that enables enterprises to implement innovation and development activities and achieve the goals in the set time, costs and required quality but they also bring risks that need to be adequately identified, analyzed and assessed. Important tools that can be used in project management in the process of risk identification are expert estimates. However, little attention is paid to determining the accuracy of expert estimates. To verify the accuracy of expert estimates, an analysis of all comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…(3) Anti-merger and acquisition risks. In many cases, well-performing companies are resistant to mergers and acquisitions, especially when they are acquired by a competitor or a hostile acquirer [13]. As a result, anti-M&A activities are easy to occur, such as seeking alternative acquirers, seeking out highquality assets, and promoting malicious liabilities, which can cause great potential risks.…”
Section: Risks At the Stage Of Merger And Acquisitionmentioning
confidence: 99%
“…(3) Anti-merger and acquisition risks. In many cases, well-performing companies are resistant to mergers and acquisitions, especially when they are acquired by a competitor or a hostile acquirer [13]. As a result, anti-M&A activities are easy to occur, such as seeking alternative acquirers, seeking out highquality assets, and promoting malicious liabilities, which can cause great potential risks.…”
Section: Risks At the Stage Of Merger And Acquisitionmentioning
confidence: 99%
“…Implementing ISO 31000:2018 can help the company reach its goal (Asmarawati & Pangeran, 2021;Selvaseelan, 2018). ISO 31000:2018 also has been proven by previous studies to be crucial in making a decision (Blokland & Reniers, 2021; Buganova et al, 2021). In terms of identifying potential risks, some studies also confirmed that ISO 31000:2018 was able to help the company identify the upcoming risks that it has to face (Mormul, 2021;Ruiz-Canela López, 2021).…”
Section: Reduce Lossesmentioning
confidence: 89%
“…In addition, it helps to build and maintain healthy and functional interpersonal relationships, which are indispensable in the process of the sustainable development of society. In addition to the tasks described above, professional sport is a very important part of the economic and economic sphere of the state, within which it creates a large number of jobs and generates economic results at local, regional and national level [1].…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, this article discusses the current situation of the sports industry in selected countries and the differences in the organisation of sport at national, regional and local levels. The aim is to show how these differences affect the possibilities of applying risk management in sport organizations and, consequently, how it is possible to proceed to the effective implementation of these elements in the management practice of sport organizations with a view to ensuring sustainable development and increasing the level of their preparedness and resilience [1], [2], [3].…”
Section: Introductionmentioning
confidence: 99%